Pressure Gauge Calibration - Pornpatkul, Chatchawan (Journal of Advanced Development in Engineering and Science, 2023)
Pressure gauge calibration using air pressure gauge as an intermediary is presented in this paper. The standard pressure gauge is calibrated in the working standard commonly used in the industry. The calibration method of DKD-R 6-1 is employed, where the error margin in measuring the pressure of the pressure gauge does not exceed the accuracy set by the factory manufacturers throughout the measurement range (±0.5% of span). At least seven variables are determined. It is found that the value of expanded uncertainty is significantly affected by some certain variables, such as the uncertainty of the calibration standard (us), the uncertainty of UUC resolution (ures) and the uncertainty of hysteresis (uhys). Furthermore, it is also found that some uncertainties can be referred and ignored in practical use, as they do not affect the expanded uncertainty. For example, the uncertainty of the local gravity (ugh), the uncertainty of the height difference between the STD and UUC (uh), the uncertainty of the zero point (uzero) and the uncertainty of repeatability (ua). The experimental results of the UUC studied in this paper show that the maximum error of measurement is +0.0037 kg/cm2 at 0.5 kg/cm2, which is in the range of accuracy specified by the manufacturer (±0.5% of span = ± 0.02 kg/cm2). Moreover, when combining the maximum error of measurement obtained from the experiment with the expanded uncertainty (Uexp) = ± 0.0132 kg/cm2, it is also found that the result is still in the accuracy specified by the manufacturer. Therefore, a calibration certificate of UUC can be issued for UUC utilization.